Pengembangan Bahan Simakan Drama Radio Berbasis Pengetahuan Lokal tentang Elit Lokal Madura untuk Siswa SMA - Faqih, Fiyan Ilman; Mutiatun, Siti (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Drama learning does not have to take the form of watching drama performances, but this learning can be done by listening to radio dramas. This research aims to produce learning media for listening to radio dramas based on local knowledge about local Madurese elites, namely kiai and blater. The method used in this research is 4D (define, design, develop, decide). The validation results from learning media experts show that the media material for watching radio dramas is suitable for implementation with a percentage score of 97%. Meanwhile, the results of the validation of literature learning also show that the learning media is suitable for implementation with 95% of participants. This learning media makes students interested in carrying out every step in operating the radio drama learning media. This is based on the results of distributing questionnaires to students who also get a percentage score of 80% -90%. Therefore, the follow-ups to this research is to carry out wider dissemination.